Ret Finger Protein: An E3 Ubiquitin Ligase Juxtaposed to the XY Body in Meiosis - Isabelle Gillot; Cédric Matthews; Daniel Puel; Frédérique Vidal; Pascal Lopez (International Journal of Cell Biology)
During prophase I of male meiosis, the sex chromosomes form a compact structure called XY body that associates with the nuclear membrane of pachytene spermatocytes. Ret Finger Protein is a transcriptional repressor, able to interact with both nuclear matrix-associated proteins and double-stranded DNA. We report the precise and unique localization of Ret Finger Protein in pachytene spermatocytes, in which Ret Finger Protein takes place of lamin B1, between the XY body and the inner nuclear membrane. This localization of Ret Finger Protein does not seem to be associated with O-glycosylation or sumoylation. In addition, we demonstrate that Ret Finger Protein contains an E3 ubiquitin ligase activity. These observations lead to an attractive hypothesis in which Ret Finger Protein would be involved in the positioning and the attachment of XY body to the nuclear lamina of pachytene spermatocytes.